PENGARUH SIFAT TANAH DAN CURAH HUJAN TERHADAP PRODUKTIVITAS KELAPA SAWIT PADA SISTEM INTEGRASI SAWIT-SAPI DI SUMATERA UTARA - Setia Sari Girsang; Erpina D Manurung; Sri H Sitindaon; Khadijah E Ramija (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2020)
The Effect of Soil and Rainfall Properties On Oil Palm Productivity In the Oil Palm-Beef Cattle Integration System. The objective is to determine the effect of soil properties and rainfall on oil palm productivity. The study was conducted in Paya Pinang Village (302'45